2002
DOI: 10.1016/s0020-7292(01)00524-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exogenous estrogen administration on serum CA‐125 originating from the endometrium

Abstract: These results suggest that endometrial CA-125 secretion to serum is dependent on the dose of administered exogenous estrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…However, for women with a uterus, Karabacak reported that 100 ug/day transdermal estradiol was associated with a significant increase in CA-125, again consistent with our results. [25] In contrast, Cengiz et al reported that current use of combination of estrogen and progestin resulted in lower CA-125 levels in women with a uterus, while Okon et al saw no change in their 12 month follow-up study. [26;27] The type of hormone therapy used was not determined in our study, but it is likely that estrogen-only therapy would predominate in the women with hysterectomy and estrogen-progestogen therapy would predominate in women with a uterus.…”
Section: Discussionmentioning
confidence: 99%
“…However, for women with a uterus, Karabacak reported that 100 ug/day transdermal estradiol was associated with a significant increase in CA-125, again consistent with our results. [25] In contrast, Cengiz et al reported that current use of combination of estrogen and progestin resulted in lower CA-125 levels in women with a uterus, while Okon et al saw no change in their 12 month follow-up study. [26;27] The type of hormone therapy used was not determined in our study, but it is likely that estrogen-only therapy would predominate in the women with hysterectomy and estrogen-progestogen therapy would predominate in women with a uterus.…”
Section: Discussionmentioning
confidence: 99%
“…Use of estrogen-alone HT was associated with lower CA125 concentrations; these associations persisted in multivariable models but were only evident among women with hysterectomy in stratified models. Administered transdermal 17ß-estradiol has previously been associated with an increase in circulating CA125 in women without hysterectomy [29] and HT use (overall; formulation not specified) was associated with higher CA125 in the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial (PLCO) [6]. However, a positive association between HT and CA125 has not been universally observed [23, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking may reduce CA125 concentrations via its effect on endogenous estrogens. Smoking is inversely associated with endogenous estrogens [44], whereas administered estradiol is associated with higher circulating CA125 [29]. Further, smoking is associated with earlier age at menopause [45], which, in turn, is associated with lower CA125.…”
Section: Discussionmentioning
confidence: 99%
“…Karabacak et al. (14) reported that 100 μ g of transdermal oestradiol significantly increased (70%) serum CA 125 levels, suggesting that the source of this increase was the endometrium, even if CA 125 levels in the study group were in the normal range. In this report, a hysteroscopy showed a thickening of endometrium, confirmed by biopsy.…”
Section: Discussionmentioning
confidence: 89%